Hacker News new | past | comments | ask | show | jobs | submit login

2 + 2 = S(S(0)) + S(1) = S(S(S(0)) + 1) = S(S(S(0)) + S(0)) - S(S(S(S(0 + 0)))) = S(S(S(S(0)))) = 4

Definiton of Successor (S) and addition. It's trivial.




How is the definition of Successor so obvious, even if you explain it? How can I understand what it so obviously means?


It's an axiom. We are talking specifically about 2+2=4 being trivial because it falls out of the axioms.

https://en.wikipedia.org/wiki/Peano_axioms




Guidelines | FAQ | Support | API | Security | Lists | Bookmarklet | Legal | Apply to YC | Contact

Search: